(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
This work is part of a research project that tries to explain both the kinds of strategies used by students and the teaching styles held by teachers concerning reading comprehension skills. The paper discusses the strategies used by 5th graders in some of Osorno schools to solve semantic, syntactic, lexical, etc. problems in their reading comprehension processing (Brown, 1985; Baker, 1991; Solé, 1999). Once the data obtained by means of a comprehension test were analysed, it was possible to hypothesise that these students lack logico-semantic integrative strategies or that they are scarcely developed as they can state the problem in terms of local coherence only (van Dijk y Kintsch, 1983). This brings together the gathering of isolated information and the incapacity to integrate information meaningfully. In the light of this evidence, it is possible to think that they have not developed conditional strategic knowledge yet (Peronard y Crespo, 1999) that may enable them to generalise and to apply this knowledge acquired at one level to other more global contexts and levels of processing.